Malaria in the returning older traveler. Issue 1 (December 2015) - Allen, N; Bergin, C; Kennelly, SP
Abstract Background Increased co-morbidities and physiological changes mean older patients may be at higher risk of adverse outcomes from certain imported illnesses. One of the most commonly diagnosed imported infections in returning travelers is malaria. Increasing age is strongly and independently associated with increasing morbidity and mortality from malaria. Delayed diagnosis leads to higher risks of poor clinical outcomes in older patients presenting with malaria. The objective of this study was to quantify malaria presentations in older patients as a percentage of total malaria presentations, compare length of hospital stay (LOS) between the older and younger cohort, and to describe medical co-morbidities, length of time to diagnosis and factors contributing to delayed diagnosis and increased LOS in the older cohort. Methods A retrospective cohort study was undertaken in two university hospitals of all patients aged 65 years or older presenting with malaria from 2002–2012. A national hospital inpatient database was used to identify patients of all ages with a discharge diagnosis of malaria over this ten year period, and quantify LOS in those aged <65 and those aged 65 years or older. The case-notes for all of the older cohort were reviewed. Results There were a total of 203 cases, 12 of whom were aged ≥65 years (5.9 %- total). Median time to diagnosis in this older group was two days (range 0–35), median LOS was eight days (range 1–77), compared to a median LOS of three days in those aged <65 years. All patients aged ≥65 years presented with fever. Travel history was documented in only 6/12 charts, and 11/12 had two or more co-morbid illnesses. Six of the 12 patients were not diagnosed or treated within 48 h of presentation. Conclusions This case series highlights the need for appropriate history-taking and timely diagnosis of the older traveler returning with fever, as delayed diagnosis and treatment can contribute to prolonged hospital stay and increased morbidity. With increasing numbers of older travelers, physicians must remain vigilant to the presence of imported illnesses, particularly malaria, in older patients with unexplained fever.